Simulation Training Using DIALux Evo Software for Estimation of Visual Comfort Level of a Building - Fahmy Rinanda Saputri; Linus Gregorius Radithya (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community outreach aims to conduct simulation training using DIALux Evo to estimate the visual comfort level in a room. Visual comfort is a crucial aspect of building design and management that can impact the occupant’s health, comfort, and productivity. However, it is often challenging for interior designers to accurately estimate the level of visual comfort. This activity involves the application of simulation technology using DIALux Evo. Participants will be provided with knowledge and skills in operating this software, covering tasks from designing rooms, placing objects, selecting building materials, and choosing artificial lighting, to analyzing, and visualizing the lighting level in a room, also will study SNI related to visual comfort. The program’s outcomes provide participants with the knowledge and skills to use DIALux Evo in estimating the visual comfort level before implementation. Finally, they can optimize space design, ensure appropriate lighting quality, and enhance the occupant’s comfort and health.